2021
DOI: 10.9734/jsrr/2021/v27i930432
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Health and Safety Risks and Hazards among Workers in the Gambian Building Construction Sites: A Mixed-Method Study Design

Abstract: Background: Providing occupational health and safety (OHS) services to employees has been a global problem for an extended period. A safe workplace should pose no avoidable risk to employees' physical, psychological, or social wellbeing and should provide opportunities for employees to improve and support their health. This study aimed to assess the occupational health and safety risks and hazards among workers at the construction sites in Kombo North District of the Gambia. Methods: A mixed-method study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Although establishing a construction company is highly regulated in the Gambia, individual workers health and safety Conversely, a study done to assess the occupational hazards among construction workers revealed a high prevalence of occupational health risks generally among building construction workers in the Gambia. 20 As such, these hazards prone workers to occupational injuries, and the effectiveness and efficiency of OHS in the construction industry in the country is still undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…Although establishing a construction company is highly regulated in the Gambia, individual workers health and safety Conversely, a study done to assess the occupational hazards among construction workers revealed a high prevalence of occupational health risks generally among building construction workers in the Gambia. 20 As such, these hazards prone workers to occupational injuries, and the effectiveness and efficiency of OHS in the construction industry in the country is still undesirable.…”
Section: Discussionmentioning
confidence: 99%
“…However, these skin conditions were not clinically examined to define a specific skin condition. The study also highlighted that workers still neglect personal hygiene practices in general, as evidenced by the dirty and torn clothes that workers wear to work and the poor condition of their shoes [35].…”
Section: Recognition Of Hazardsmentioning
confidence: 96%